Deontological aspects of the nursing profession: understanding the code of ethics - Terezinha Nunes da Silva; Maria Eliane Moreira Freire; Monica Ferreira de Vasconcelos; Sergio Vital da Silva Junior; Wilton José de Carvalho Silva; Patrícia da Silva Araújo; Allan Victor Assis Eloy
ABSTRACT Objective: to investigate nursing professionals' understanding concerning the Code of Ethics; to assess the relevance of the Code of Ethics of the nursing profession and its use in practice; to identify how problem-solving is performed when facing ethical dilemmas in professional practice. Method: exploratory descriptive study, conducted with 34 (thirty-four) nursing professionals from a teaching hospital in João Pessoa, PB - Brazil. Results: four thematic categories emerged: conception of professional ethics in nursing practice; interpretations of ethics in the practice of care; use of the Code of Ethics in the professional practice; strategies for solving ethical issues in the professional practice. Final considerations: some of the nursing professionals comprehend the meaning coherently; others have a limited comprehension, based on jargon. Therefore, a deeper understanding of the text contained in this code is necessary so that it can be applied into practice, aiming to provide a quality care that is, above all, ethical and legal.